2015
DOI: 10.1159/000371587
|View full text |Cite
|
Sign up to set email alerts
|

Single-Dose Rituximab for Recurrent Glomerulonephritis Post-Renal Transplant

Abstract: Background/Aims: Post-renal transplant recurrent glomerulonephritis (GN) contributes to allograft loss. Rituximab treatment has been used in a multidose strategy with variable efficacy and toxicity. We investigated a novel single-dose approach. Methods: A single center, retrospective, cohort study was conducted between January 1998 and April 2012 among renal allograft recipients with recurrent GN treated with rituximab (cases) or without (controls). The primary outcome was complete response (CR, urine protein/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…We administered rituximab 200 mg intravenously, once. This low-dose was chosen because of our experience with efficacy with this dose for other recurrent glomerulonephritidies and others have reported that even 100 mg can successfully treat recurrent FSGS ( 13 16 ).…”
Section: Resultsmentioning
confidence: 99%
“…We administered rituximab 200 mg intravenously, once. This low-dose was chosen because of our experience with efficacy with this dose for other recurrent glomerulonephritidies and others have reported that even 100 mg can successfully treat recurrent FSGS ( 13 16 ).…”
Section: Resultsmentioning
confidence: 99%
“…The apparent lack of adverse impact of MN on patient survival despite poorer death-censored kidney allograft survival in our study might be related to improvements in immunosuppressive therapy. The anti-PLA2R antibody in the serum is unlikely to have had an impact as the study period was prior to the introduction of this antibody in clinical practice [22, 3638]. Patients with MN also had a number of favorable characteristics for survival, including greater frequency of early renal service referral and a higher likelihood of pre-emptive kidney transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…The authors advocate laboratory monitoring with CD19 B cell count, whose depletion occurs a few weeks after the administration of rituximab and/or blood levels of anti-PLA2R in MN associated with this antigen 76 . In this review 76 , the authors describe a total of 57 cases of MN recurrence in some references 63,[67][68][69][70][78][79][80] , and there are reports of additional cases in other publications [81][82][83] . There are no other immunosuppressive therapies that have been shown to be more effective.…”
Section: Relapsing Mnmentioning
confidence: 99%